AB0322 Evaluation of Vaccines in Rheumatoid Arthritis: Data from the COMORA Study. (10th June 2014) - Hmamouchi, I.; Winthrop, K.; Launay, O.; Dougados, M.
Abstract : Background: Rheumatoid Arthritis (RA) patients are at risk of suffering from infectious diseases including those of the respiratory tract. Such risk seems to be higher in RA than in the general population. Although vaccines have proven effective in RA patients, they are little used today. Objectives: Our objectives were: (1) to describe the vaccines status of pneumococcus and influenza in patients with RA from different countries (2) to identify factors influencing pneumococcal or influenza vaccinations. Methods: Study design: This was an ancillary study from COMORA cohort [1], including 3920 RA patients consecutively. Data collected: The demographic and disease characteristics data were collected. The time of the last pneumococcal vaccination and influenza was recorded using a questionnaire. Data analysis: Univariate and multivariate analysis was performed by SPSS 10.0. Results: The rate of vaccination coverage was low with huge disparities between countries: 636 patients (17.2%) for pneumococcal vaccination (from 0% in Morocco to 56.5% in Egypt) and 938 patients (25.3%) for influenza vaccination (from 1% in Egypt to 66.2% in Japan). In multivariate analysis, factors associated with pneumococcal vaccination less than 5 years were: age>65 years (OR=1.4, CI95% (1.1-1.8), p=0.003), absence of steroids (OR=1.4, CI95% (1.1-1.7), p=0.004), country (p<0.0001), the high level of education (OR=1.6, CI95% (1.1-2.3), p=0.003), lung disease (OR=1.7, CI95% (1.1-2.5), p=0.006) and kidney disease (OR =2.0, CI 95% (1.1-3.5), p=0.01). In multivariate analysis, factors associated with influenza vaccination less than one year were: age>65 years (OR=1.8, CI 95% (1.5-2.2), p<0.0001), DAS28 <3.2 (OR=1.2, CI95% (1.0-1.4), p=0.04), any treatment intake for another disease (OR=1.4, CI95% (1.1-1.7), p<0.001), history of surgery related to RA (OR=1.5, CI95% (1.2-2.1), p<0.0001) and country (p<0.0001). Conclusions: This study suggests a low coverage rates of vaccinations despite international recommendations with a huge disparity between countries. Identification of factors associated with the vaccine status might facilitate the improvement of such coverage References: Dougados M, Soubrier M, Antunez A, et al. Prevalence of comorbidities in rheumatoid arthritis and evaluation of their monitoring: results of an international, cross-sectional study (COMORA). Ann Rheum Dis. 2014 Jan 1;73(1):62-8. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3339